A Comparative Study of Gas Turbine Power Plant and Renewable Solar Energy and Regulatory Frameworks in Libya - Ali Ahmed Aboukra; Khaled Al Hadi Lekhmaisi (African Journal of Advanced Pure and Applied Sciences, 2024)
Energy systems in Libya present inherent characteristics like any energy systems in the third-world countries which meanly depend on classical generation systems of electricity such as fossil and gas. This leads to high electricity prices, heavy dependence on fuel, pollution and carbon emissions. In recent years, the development of renewable energy technologies has presented an opportunity to counter these challenges and improve the affordability and sustainability of energy systems. This study focuses on a gas turbine power plant compared to a solar PV power station. the uptake of this has been constrained by various factors. These include consumption quantities of fuel, installations, operations and maintenance cost-effective, CO2 emissions, and available land area. This study compares the gas turbine power plant and renewable solar energy systems in Libya, analyzing their impact on electricity prices, fuel dependence, pollution, and carbon emissions.